MitraClip for mitral valve regurgitation and transcatheter aortic valve implantation for severe aortic valve stenosis: state-of-the-art - Tokarek, Tomasz; Dziewierz, Artur; Dudek, Dariusz (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
There is a worldwide expansion in percutaneous therapy for valvular heart disease. Rapidly evolving technology and the general increase in life expectancy will support the evolution of new treatment options dedicated to structural heart interventions. Transcatheter aortic valve implantation for severe aortic valve stenosis and percutaneous mitral valve repair with the MitraClip system for severe mitral regurgitation have been demonstrated as a feasible, innovative alternative for surgical treatment. Despite the inequality in clinical experience, both procedures have encouraging results and now are a part of everyday clinical practice. More importantly, rapid development is expected in the next decades. However, the global coronavirus disease 2019 (COVID-19) pandemic imposed redistribution of healthcare resources. Hospitals were obliged to modify their workflow and limit TAVI and MitraClip procedures to urgent or in highly symptomatic patients. Despite this encumbrance improvement in technology and experience supported by robust evidence from current studies might extend indications for both procedures. The future holds promise for this treatment modality to become the preferred procedure for all patients despite age or risk and reserving surgical treatment for a minority. Thus, we present state-of-the-art and current evidence for both methods assumed to change the paradigm of treatment of valvular heart failure in the future.